2013
DOI: 10.1038/ng.2824
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study using cellular traits identifies a new regulator of root development in Arabidopsis

Abstract: With the increased availability of high-resolution sequence information, genome-wide association (GWA) studies have become feasible in a number of species. The vast majority of these studies are conducted in human populations, where it is difficult to provide strong evidence for the functional involvement of unknown genes that are identified using GWA. Here we used the model organism Arabidopsis thaliana to combine high-throughput confocal microscopy imaging of traits at the cellular level, GWA and expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
116
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 34 publications
0
116
1
Order By: Relevance
“…The currently available large populations, dense genotyping, and the advantage of homozygous lines in the mainly self-fertilizing species Arabidopsis, ought to greatly enhance the power of such studies. Indeed, GWA studies confirmed many of the previously identified genes in experimental mapping populations and mutant studies and detected a number of, to our knowledge, novel candidate genes, although this is limited for quantitative traits (Atwell et al, 2010;Brachi et al, 2010;Li et al, 2010;Todesco et al, 2010;Chan et al, 2011;Chao et al, 2012;Filiault and Maloof, 2012;Sterken et al, 2012;Yano et al, 2013;Chao et al, 2014;Meijón et al, 2014;Bac-Molenaar et al, 2015). Similar to the problem of missing heritability in human GWA studies, where individual variants cannot explain the phenotypic variation despite high heritabilities (Yang et al, 2010;Gibson, 2011;Makowsky et al, 2011), genetic variants cannot fully explain the high heritabilities in plant studies (Brachi et al, 2010;Sasaki et al, 2015).…”
mentioning
confidence: 55%
“…The currently available large populations, dense genotyping, and the advantage of homozygous lines in the mainly self-fertilizing species Arabidopsis, ought to greatly enhance the power of such studies. Indeed, GWA studies confirmed many of the previously identified genes in experimental mapping populations and mutant studies and detected a number of, to our knowledge, novel candidate genes, although this is limited for quantitative traits (Atwell et al, 2010;Brachi et al, 2010;Li et al, 2010;Todesco et al, 2010;Chan et al, 2011;Chao et al, 2012;Filiault and Maloof, 2012;Sterken et al, 2012;Yano et al, 2013;Chao et al, 2014;Meijón et al, 2014;Bac-Molenaar et al, 2015). Similar to the problem of missing heritability in human GWA studies, where individual variants cannot explain the phenotypic variation despite high heritabilities (Yang et al, 2010;Gibson, 2011;Makowsky et al, 2011), genetic variants cannot fully explain the high heritabilities in plant studies (Brachi et al, 2010;Sasaki et al, 2015).…”
mentioning
confidence: 55%
“…The putative function of these genes was confirmed by an analysis of T-DNA lines, showing that AT has the potential to uncover new links between metabolic and/or regulatory pathways. In Arabidopsis, GWAS approaches also recovered previously known candidate genes (Aranzana et al, 2005;Atwell et al, 2010;Chan et al, 2011;Chao et al, 2012), but reports of new discoveries are still scarce (Angelovici et al, 2013;Meijón et al, 2014;Verslues et al, 2014).…”
Section: Power Of Atmentioning
confidence: 99%
“…Allelic variation of this gene, coined KURZ UND KLEIN, determines a large fraction of variance for two highly correlated traits: meristem length and mature cell length (Meijón et al, 2014). The major portion of this effect was caused by sequence variation in the coding region of the KURZ UND KLEIN gene (Meijón et al, 2014). Using GWAS for 16 root growth traits on each day of a 5-d time course, 35 highly significant associations could be detected.…”
Section: Using Natural Variation To Identify Regulators Of Root Growtmentioning
confidence: 97%
“…Later analysis suggested that BRX is also involved in cytokinin-mediated inhibition of LR development (Li et al, 2009) and furthermore, the auxin-cytokinin cross talk that coordinates cell division and differentiation in the root tip (Scacchi et al, 2010). Combining high-throughput confocal microscopy imaging, GWAS, and expression analysis, a then-uncharacterized gene encoding an F-box protein was found that underlies the natural variation of root development in a broad set of accessions (Meijón et al, 2014). Allelic variation of this gene, coined KURZ UND KLEIN, determines a large fraction of variance for two highly correlated traits: meristem length and mature cell length (Meijón et al, 2014).…”
Section: Using Natural Variation To Identify Regulators Of Root Growtmentioning
confidence: 99%
See 1 more Smart Citation